Impact of ZrO2 and Si3N4 Ceramics Dispersion on the Ti6Al4V Matrix: Mechanical and Microstructural Characteristics Using SPS - Anthony O. Ogunmefun; Emmanuel R. Sadiku; Linda M. Teffo; Williams K. Kupolati (Crystals, 2025)
This study investigates the effect of duo-ceramic zirconia and silicon nitride (ZrO2-Si3N4) particles and their reinforcement proficiencies on a Ti6Al4V alloy, consolidated using the spark plasma sintering (SPS) technique. The selected sintering parameters are, viz., 900 °C temperature, 50 MPa pressure, 10 min of holding time, and 100 °C/min of sintering rate. SEM/EDS and XRD equipment were used to disclose the microstructural evolution and phase identification of created composites. The mechanical characteristics of the resulting composites were determined using the nanoindentation technique. All consolidated sintered composites showed excellent densification, with sample relative densities reaching 96.65%. Significant improvements were also made in their nanomechanical characteristics; among the composite samples with different volume fractions, the ceramics with the lowest volume percentage had the best mechanical characteristics, whereas the sintered samples with the highest ceramic volume percentage showed a decrease in mechanical proficiencies and relative density. Composite S1, with the lowest volume fraction of the duo-ceramic particles, was seen to have a significant mechanical property improvement better than other composites, S2 and S3, in terms of measured Vickers microhardness, elastic modulus, and nano hardness values at a sintering temperature of 900 °C. Consequentially, composite specimens S2 and S3’s mechanical characteristics and relative densities dropped as the volume fractions of the duo-ceramic particles increased.